Fish Catch Variations and Associated Variables among Fishermen Operating Plank-Built Crafts - S., Balasubramanian; M.P., Ramesan; Gopal, Nikita (Fishery Technology, 2025)
The fish catch variations in terms of the quantity of catch per day and the socio-personai variables of fishermen operating plank-built crafts (15-17 m) were analysed in three fishing centres. Of the 15 socio-personal variables, there were no significant differences between the artisanal fishermen respondents. The overall average fish catch for three centres varied between 526.81 to 533.46 kg per day of fishing among the fishermen and statistically, the fish catch differences were not significant between the fishing centres over a period of five months. In the correlation analysis, five variables viz., investment on craft, investment on net, investment on engine, size of fishing net used and total engine hp used were found to have significant positive correlation with the fish catch variation levels. In the regression analysis, R2 value was high (74.11%) and non-significant. Further, the independent variables including the fish catch variation levels did not have significant positive association with the innovation proneness index scores.